Modelling the Information Content in Insider Trades in the Singapore Exchange - WONG, K. A. (Institutional Knowledge at Singapore Management University, 2005)
Over the past decade, numerous studies have debated the usefulness of insider trading. One particularly important study relates to the informational role that insiders’ transaction volumes have on trading activity in the equity market. In our paper, we examine whether insiders’ purchases (sales) indicate positive (negative) earnings announcements. We argue that if insiders have early access to publicly announced information, then the issuance of good (bad) news should be preceded by insider buying (selling) activities. The results reveal that insiders’ trading volume play an important role in the dissemination of private information to the investing public. In particular, insiders’ purchases (sales) are found to be a good indication of good (bad) news. The information content in insiders’ trades may be exploited, provided investors are able to realize returns within one, and at most two months, after the announcement date.